Biology and development of protocols for culturing soil-dwelling endogeic worm Pontoscolex corethrurus Muller for potential use in soil rehabilitation - Kok, Ho Yin (2014)
Pontoscolex corethrurus (Müller, 1857) is the dominant tropical soil-dwelling endogeic worm and has the ability to live in a variety of soils differing in pH and organic matter content. This suggestedthat this species may serve as a potential agent for soil rehabilitation particularly in the tropics. Unfortunately, the relevant information about P. corethrurus is very limited in Malaysia. A detailed understanding of life history of P. corethrurus is required because the biological characteristics of earthworms (e.g., growth and reproduction rates) could affect their potential in soil rehabilitation programs. The rates of growth and reproduction of P. corethruruson different stocking densities were also evaluated to determine the optimum stocking density for culturing this species. This study discovered that the optimum stocking for culturing P. corethruruswas around 200 earthworms per m2. This study also reported that P. corethrurus has a high survival rate and has the capability to reproduce via parthenogenesis. These biological characteristics enable P. corethrurus to colonize new environments hence, increasing its potential for the use in worm inoculation activities. In order to obtain a large and consistent supply of earthworms for worm inoculation activities in soil rehabilitation, indoor culturing of P. corethrurus is crucial. However, there are difficulties in using natural soil as the medium for culturing endogeic worms due to the heterogeneous nature of soils in different localities that will surely affect the culture performance. Thus, a protocol was developed using artificial soil to replace nature soil for culturing P. corethrurus. This study found that clay content can affect the growth of P. corethrurus and the manipulation of the clay content in artificial medium (consists of kaolinite clay, industrial quartz sand and decomposed cow dung) could result it as an alternative medium for culturing P. corethrurus. Furthermore, the properties of earthworm surface cast, worm-worked soil and bulk soil (soil without earthworm inoculation) were analyzed to study the influence of P. corethrurus activities on soil properties. Earthworm surface cast and worm-worked soil recorded significantly higher amounts of available nutrients than bulk soil. Soil enzymes (protease and acid phosphatase) activities, microbial (bacteria) population and humic acid content were also significantly higher in earthworm cast than in bulk soil. A subsequent polybag-plant experiment was conducted to determinehow the presence of P. corethrurus in soil could benefit plant productivity. With the application of organic amendment, the inoculation of P. corethrurus into the planting medium (+E+O treatment) significantly increased plant height (20%), root (27%) and shoot (37%) dry weights as well as crop yield (15%) compared to treatment without earthworm inoculation (–E+O treatment). The present study suggested that the tropical soil-dwelling endogeic worm P.corethrurus can be considered as a good soil rehabilitation agent for rehabilitating soil and increasing plant productivity.